Substance P‐induced lung inflammation in mice is mast cell dependent. Issue 1 (23rd June 2021) - Wang, Nan; Wang, Jue; Zhang, Yongjing; Hu, Shiling; Zhang, Tianxiao; Wu, Yuanyuan; Sun, Xiuzhen; Zhang, Tao; Yang, Shuanying; He, Langchong
Abstract: Background: Allergic asthma is a common inflammatory lung disease and a major health problem worldwide. Mast cells (MCs) play a key role in the early‐stage pathophysiology of allergic asthma. Substance P (SP) functions in neurogenic inflammation by activating MCs, and therefore, it may to participate in the occurrence and development of asthma. Objective: We examined the relationship between SP and lung inflammation, and also whether SP can directly trigger asthma. Methods: We measured the number of peripheral blood eosinophils, neutrophils and basophils and evaluated the levels of IgE and SP in blood samples of 86 individuals with allergic asthma. Serum IgE and SP levels were also determined in 29 healthy individuals. C57BL/6 mice were subjected to different doses of SP, and bronchoalveolar lavage fluid (BALF) was collected to count the inflammatory cells. Lung tissues were analysed using histopathological methods to evaluate lung peribronchial inflammation, fibrosis and glycogen deposition. Levels of IgE, interleukin (IL)‐1, IL‐2, IL‐4, IL‐5, IL‐13, IL‐17 and IFN‐γ were determined in mouse serum. Results: Substance P levels were increased in the serum samples of patients with asthma. SP induced mouse lung peribronchial inflammation, fibrosis and glycogen deposition, with high levels of Th2‐related cytokines such as IL‐4, IL‐5 and IL‐13 observed in the BALF. Furthermore, low level of total IgE was noted in the serum, and SP had little effect on MC‐deficient kit W‐sh/W‐sh mice. Conclusions & clinical relevance: Substance P levels increased significantly in serum of asthmatic patients and independently associated with the risk of asthma. Furthermore, SP induced Th2 lung inflammation in mice, which was dependent on MCs. Abstract : Here, we found that SP levels were increased in the serum samples of patients with asthma, which was independently associated with the risk of asthma. In mice model, SP induced lung peribronchial inflammation, fibrosis, and glycogen deposition, with high levels of Th2‐related cytokines in the BALF. Furthermore, low level of total IgE was noted in the serum, and SP had little effect on MC‐deficient kit W‐sh/W‐sh mice, which indicated that SP induced Th2 lung inflammation in mice was dependent on MCs.